Contribution to carrier detection and genetic counselling in X linked retinoschisis. Issue 6 (June 1991) - Kaplan, J; Pelet, A; Hentati, H; Jeanpierre, M; Briard, M L; Journel, H; Munnich, A; Dufier, J L
Abstract : X linked retinoschisis (RS) is a vitreoretinal disease resulting from microcystic degeneration of the macula associated with peripheral lesions. The disease gene has already been assigned to the distal short arm of the X chromosome (Xp22.2) by linkage studies. In order to contribute both to a better localisation of the RS locus and to genetic counselling in RS families, we have carried out a clinical and genetic analysis in seven pedigrees. We show, first, that in contrast with previous reports, heterozygote carriers frequently express the disease, and display peripheral retinal alterations similar to those found in affected males. Second, while distal markers DXS16, DXS207, and DXS43 are closely linked to the disease locus, a high level of recombination events was found with centromeric markers, namely DXS274, DXS41, and DXS164. These findings must be taken into account for both carrier detection and prenatal diagnosis in X linked RS.